Htr2a Gene and 5-HT2A Receptor Expression in the Cerebral Cortex Studied Using Genetically Modified Mice - Andrade, Rodrigo; Weber, Elaine T. (Frontiers in Neuroscience, 2010)
Serotonin receptors of the 5-HT2A subtype are robustly expressed in the cerebral cortex where they have been implicated in the pathophysiology and therapeutics of mental disorders and the actions of hallucinogens. Much less is known, however, about the specific cell types expressing 5-HT2A receptors in cortex. In the current study we use immunohistochemical and electrophysiological approaches in genetically modified mice to address the expression of the Htr2a gene and 5-HT2A receptors in cortex. We first use an EGFP-expressing BAC transgenic mice and identify three main Htr2A gene expressing neuronal populations in cortex. The largest of these cell populations corresponds to layer V pyramidal cells of the anterior cortex, followed by GABAergic interneurons of the middle layers, and non-pyramidal cells of the subplate/Layer VIb. We then use 5-HT2A receptor knockout mice to identify an antibody capable of localizing 5-HT2A receptors in brain and use it to map these receptors. We find strong laminar expression of 5-HT2A receptors in cortex, especially along a diffuse band overlaying layer Va. This band exhibits a strong anteroposterior gradient that closely matches the localization of Htr2A expressing pyramidal cells of layer V. Finally we use electrophysiological and immunohistochemical approaches to show that most, but not all, GABAergic interneurons of the middle layers are parvalbumin expressing Fast-spiking interneurons and that these cells are depolarized and excited by serotonin, most likely through the activation of 5-HT2A receptors. These results clarify and extend our understanding of the cellular distribution of 5-HT2A receptors in the cerebral cortex.